Innovative education system and tolerance skills - Qaharov Salohiddin Najmiddin oglu; Shernazarov Khushnudbek Sunnatillo ogli (Genius Journals, 2021)
In modern society, the role of spiritual and moral education in human development is particularly great. In recent years, researchers pay much attention to the search for new methods and approaches in education. The creation of a new concept of education has a paramount importance. The education system should be integrated into the global educational community and to respond to global trends in education. The primary focus of educational innovations should be on teaching and learning theory and practice, as well as on the learner, parents, community, society, and its culture. Technology applications need a solid theoretical foundation based on purposeful, systemic research, and a sound pedagogy. One of the critical areas of research and innovation can be cost and time efficiency of the learning
Keywords: Tolerance; education; innovation system; upbringing